Mestre gamela: trajetória e reflexões sobre uma escola de violão popular - Afiune Júnior, Felício José (2019)
This research focuses on documenting historical facts related to Mestre Gamela's trajectory and proposing reflections about his musical conception and guitar teaching method. Sidney Barros (1943-2013), known as Mestre Gamela, was one of the most important guitarists in the Brazilian scene (1971-2013). His performance influenced a generation of musicians and helped to train several renowned instrumentalists in Brazil and abroad, among them: Lula Galvao, Nelson Faria, Genil Castro, Rosa Passos, Reco do Bandolim, Hamilton de Holanda, Gabriel Grossi, Tom Capone, Daniel Santiago, Zélia Duncan, Cassia Eller, Herbert Viana. Given the peculiarities of his teaching method and the size of his influence, it is considered that the work developed by Mestre Gamela is configured as a guitar school. This research aims to promote the visibility of this important Brazilian guitarist and provide significant empirical data for research on guitar studies and popular music. From information collected in interviews and various sources, this study presents a contextualized narrative of important events related to the musician's education, his professional experiences and his pedagogical performance in Brasilia. Based on an interdisciplinary approach involving assumptions of Phenomenology, Cultural History, Musicology and Musical Analysis, several aspects of Mestre Gamela's performance were investigated. The following procedures were performed: mapping of the material produced by the musician (publications and manuscripts); verification of the characteristics of his conception of music and its teaching; research on what Gamela was doing its activities for; analysis of part of their arrangements. By articulating information about Gamela's trajectory and performance, it was possible to unveil various obscurities about the process of development of her teaching method and to outline a set of practices and technical and stylistic elements that make up her School of popular guitar.